Loong Patterns in Ancient Dongyang Houses Cultural Significance and Morphological Development - Guo, Xiaotian; Faridah, Sahari (Transnational Press London Ltd, 2025)
This study examines the physical evolution and cultural symbolism of the loong designs found in Dongyang's historic homes. Chinese loongs are very distinct from Western dragons and are significant in traditional culture. The study examined its application distribution, loong pattern types (Kui, Chi, etc.), and architectural aspects (layout, structure, decoration, etc.). Combining the shifts in the artistic qualities and cultural significance of loong patterns over time, from mysterious and authoritative to royally exclusive, with the morphological evolution of loong patterns from the Shang and Zhou Dynasties to the Ming and Qing Dynasties, such as the Shang and Zhou Kui loong patterns, the Qing Dynasty Chi loong pattern, and other corresponding characteristics. The conclusion demonstrates that the loong pattern of Dongyang ancient dwellings is an important part of traditional architectural decorative art, carrying profound cultural significance. This is achieved by combining the morphological evolution of loong patterns from the Shang and Zhou Dynasties to the Ming and Qing Dynasties, such as the Shang and Zhou Kui loong patterns, the Qing Dynasty Chi loong pattern, and other respective characteristics, with the changes in the artistic characteristics and cultural significance of loong patterns in different periods, from mysterious and authoritative to royal exclusive, etc. Its development is important for understanding historical culture and passing down architectural ornamental art, and it reflects aesthetic and social shifts. Keywords: Ancient Dongyan, Morphological Development, Ming and Qing Dynasties